Entrepreneurial women's cognitive ambidexterity: Career and cultural influences - M. J.de Villiers Scheepers; C. Boshoff; M. Oostenbrink (South African Journal of Business Management, 2017)
The purpose of this study was to examine how women's career stage and Ubuntu (collectivist) values relate to their cognitive ambidexterity when pursuing entrepreneurial initiatives in multicultural South Africa. In this study individual cognitive ambidexterity was operationalised as using effectual and causal logic. More than three hundred businesswomen from diverse backgrounds were surveyed. The results revealed that career stage, self-efficacy and Ubuntu collectivism are important in women's ambidexterity. Mature, efficacious women in their late career stage draw on their diverse networks and use effectual affordable loss, flexibility and causation when pursuing entrepreneurial initiatives. In contrast, younger, early-career women are more likely to use pre-commitment to ensure support from stakeholders. Women with Ubuntu values use their relationship skills to draw on resources from their networks and use ambidexterity (effectual and causal logic) in their entrepreneurial endeavours.The findings suggest that entrepreneurial women who develop their cognitive ambidexterity and draw on both effectual and causal approaches when initiating entrepreneurial initiatives are more likely to experience successful outcomes. These mental approaches can be developed by means of awareness, training and mentoring. This study extends the literature on women's entrepreneurial decision-making in a culturally diverse society, demonstrating the influence of cultural values and career stage on effectual and causal logic.
Keywords: 650